Corporate governance for Islamic banking sustainability and caux round table principles - Mohd. Israil, Khaliq Ahmad (ISTAC, 2015)
Corporate Governance for Islamic Banking Sustainability and Caux Round Table Principles is an attempt to give a balanced view of both Western and Islamic perspectives. The review of the literature, explanations of the verses of the Qur’an that relate to corporate governance (CG) theories and Islamic perspective to it will enrich the field. This paper takes those traditional theories in literature and interprets them from an Islamic perspective, using more international perspectives especially for the Muslim world. Since failure to make profit alone is not enough reason of defaulting corporate entities rather non-compliance of shari’ah and Islamic ethical guidelines and lack of CSR concern is equally important in defining failure